External Liabilities and Crises - Catao, Luis (IMF Working Papers; Working Paper, 2013)
We examine the determinants of external crises, focusing on the role of foreign liabilities and their composition. Using a variety of statistical tools and comprehensive data spanning 1970-2011, we find that the ratio of net foreign liabilities (NFL) to GDP is a significant crisis predictor, and the more so when it exceeds 50 percent in absolute terms and 20 percent of the country-specific historical mean. This is primarily due to net external debt--the effect of net equity liabilities is weaker and net FDI liabilities seem if anything an offset factor. We also find that: i) breaking down net external debt into its gross asset and liability counterparts does not add significant explanatory power to crisis prediction; ii) the current account is a powerful predictor, either measured unconditionally or as deviations from conventionally estimated 'norms' iii) foreign exchange reserves reduce the likelihood of crisis more than other foreign asset holdings; iv) a parsimonious probit containing those and a handful of other variables has good predictive performance in- and out-of-sample. The latter result stems largely from our focus on external crises stricto sensu.